Experimental Study of Vibration Suppression Technique of Planetary Gear System based on Planet Phasing - An Wendi; Zhang Xiaoxu; Wang Xin; Ji Xiubin (Jixie chuandong)
Based on planet phasing theory research,two groups 30 kW single stage double helical tooth planetary gear transmission system with different meshing phase characteristics are designed and manufactured.The vibration and noise signals of the two groups systems are collected under the same working condition by comparing test method.The obtained data is analyzed,and the effectiveness of the vibration and noise reduction of "vibration suppression technique of planetary gear system based on planet phasing"is verified.The results show that the vibration and noise of the gear mesh in the planetary transmission system can be effectively reduced by the planet phasing theory.